Metal complex ink, manufacturing method of metal complex ink, and manufacturing method of metal particles

JP2025034017APending Publication Date: 2025-03-13SUMITOMO METAL MINING CO LTD +1

Patent Information

Application Number
JP2023140133
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

Smart Images

  • Figure 2025034017000001_ABST
    Figure 2025034017000001_ABST
Patent Text Reader

Abstract

To provide a metal complex ink with stable metal complex characteristics, capable of controlling a variation in a size or a shape of metal particles, a manufacturing method of a metal complex ink, and a manufacturing method of metal particles.SOLUTION: A metal complex ink includes: colloids with micelles of a metal complex expressed by (HCOO)2Me(2EHA)2 aggregated; and an ethylene glycol with the colloids dispersed. In the metal complex ink, the Me is Cu or Ni, and the 2EHA is 2-ethyl hexylamine.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal complex ink, a method for producing a metal complex ink, and a method for producing metal particles. [Background technology]

[0002] In recent years, printed electronics has been developed as a wiring technology for semiconductor elements, electronic circuits, etc. Printed electronics has attracted attention because it can reduce manufacturing costs compared to existing semiconductor manufacturing technologies such as photolithography.

[0003] Inks using complexes have been developed as inks for such printed electronics (see, for example, Non-Patent Documents 1 and 2). According to Non-Patent Document 1, by using copper particles and a silver complex, it is possible to realize metal wiring having a core-shell structure in which copper particles are covered with a copper-silver alloy. According to Non-Patent Document 2, by using a copper complex and a silver complex, it is possible to realize metal wiring made of a copper-silver alloy. In all of these, by forming a copper-silver alloy, oxidation resistance is improved compared to metal wiring made of copper alone, but further improvement is required for practical use. In addition, unevenness, bumps, and cracks may occur on the electrodes during use, and stability is not sufficient. In addition, since the material contains silver, it is expensive.

[0004] Nickel particles are also used for electrodes because they are more chemically stable than copper particles and less expensive than silver particles (see, for example, Patent Document 1). Patent Document 1 discloses that nickel particles can be obtained from a nickel complex obtained from nickel formate dihydrate and an aliphatic amine, and reports that the particle size of the nickel particles can be controlled by changing the chain length of the alkyl group of the aliphatic amine.

[0005] Copper nanoparticles having a nickel-copper alloy in the surface layer have been developed (see, for example, Patent Document 2). Patent Document 2 discloses that the nickel-copper alloy in the surface layer improves oxidation resistance, and that the nanoparticles can be used for fine wiring by printing or coating methods. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2010-064983 A [Patent Document 2] JP 2011-063828 A [Non-patent literature]

[0007] [Non-Patent Document 1] Wanli Li et al.,ACS Appl.Mater.Interfaces,2017,9,24711-24721 [Non-Patent Document 2] Wanli Li et al., Nanoscale, 2018, 10, 5254 Summary of the Invention [Problem to be solved by the invention]

[0008] However, in metal complex inks containing metal complexes, the properties of the metal complex change and become unstable over time after the production of the metal complex ink, which can result in variations in the particle size and shape of the metal particles obtained by heating the metal complex ink, and as a result, there is a risk that the performance of semiconductor elements and the performance of wiring in electronic circuits, etc. may become unstable.

[0009] Therefore, an object of the present invention is to provide a metal complex ink, a method for producing a metal complex ink, and a method for producing metal particles, in which the properties of the metal complex are stable and the variations in the particle size and shape of the metal particles can be controlled. [Means for solving the problem]

[0010] In order to solve the above problems, the metal complex ink of the present invention is a metal complex ink comprising a colloid formed of micelles of a metal complex represented by (HCOO)2Me(2EHA)2, and ethylene glycol in which the colloid is dispersed, wherein the Me is Cu or Ni, and the 2EHA is 2-ethylhexylamine.

[0011] The metal complex may be (HCOO)2Cu(2EHA)2, (HCOO)2Ni(2EHA)2, or a mixture of (HCOO)2Cu(2EHA)2 and (HCOO)2Ni(2EHA)2.

[0012] The metal complex ink may have a water content of 20% by mass or less, and an ethanol content of 50% by mass or less.

[0013] In order to solve the above problems, the method for producing a metal complex ink of the present invention comprises the steps of: m The method includes a first mixing step of mixing a metal formate represented by Me·nH2O, ethylene glycol, and 2-ethylhexylamine, wherein Me is either Cu or Ni, m is 2 when Me is Cu or Ni, n is 4 when Me is Cu, and is 2 when Me is Ni.

[0014] a second mixing step of mixing the metal formate with ethanol before the first mixing step; The first mixing step may be followed by a dehydration step of dehydrating the mixture obtained in the first mixing step under reduced pressure.

[0015] The metal formate may be solely (HCOO)2Cu·4H2O or solely (HCOO)2Ni·2H2O.

[0016] In addition, in order to solve the above-mentioned problems, the method for producing metal particles of the present invention includes a heating step of heating the metal complex ink of the present invention, which decomposes the metal complex to obtain metal particles and removes ethylene glycol.

[0017] In order to solve the above problems, the manufacturing method for a metal sintered film of the present invention includes a printing step of printing the metal complex ink of the present invention into a thin film, and a heating step of heating the thin film obtained by the printing step in nitrogen gas and holding it at 250°C for 10 minutes to obtain a metal sintered film. Effect of the Invention

[0018] According to the present invention, it is possible to provide a metal complex ink in which the properties of the metal complex are stable and the variations in the particle size and shape of the metal particles can be controlled, a method for producing a metal complex ink, and a method for producing metal particles.

[0019] In addition, the present invention can control the variations in particle size and shape of metal particles, thereby stabilizing the performance of semiconductor elements and the performance of wiring in electronic circuits and the like. Furthermore, it can provide a metal complex that is useful as a material for internal electrodes of laminate components such as multilayer ceramic capacitors (MLCCs) and varistors, and electronic components such as inductor coils. [Brief description of the drawings]

[0020] [Figure 1] 1 is an image of the copper complex ink and copper particles of Example 1 taken with an optical microscope. [Diagram 2] 1 is an image of the copper complex ink and copper particles of Comparative Example 1 taken with an optical microscope. [Diagram 3] 1 is an image of copper particles of Example 1 taken by SEM. [Figure 4] 1 is an image of copper particles of Comparative Example 1 taken by SEM. [Diagram 5] 1 is a cross-sectional image of a copper sintered film formed by heating at 250° C. using the copper complex ink of Example 1, taken with an SEM. [Figure 6] 1 is a cross-sectional image of a copper sintered film formed by heating at 250° C. using the copper complex ink of Comparative Example 1, taken with an SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the metal complex ink, the method for producing a metal complex ink, and the method for producing metal particles of the present invention will be described.

[0022] [Metal complex ink] The metal complex ink of the present invention contains a colloid formed by aggregation of micelles of a metal complex represented by (HCOO)2Me(2EHA)2, and ethylene glycol in which the colloid is dispersed. In the metal complex ink, the metal complex is in the form of micelles (i.e., colloidal particles), and a plurality of these micelles aggregate to form a colloid, which is dispersed in ethylene glycol.

[0023] In the metal complex, the Me is Cu or Ni and the 2EHA is 2-ethylhexylamine.

[0024] That is, the metal complex is a copper formate complex ((HCOO)2Cu(2EHA)2) or a nickel formate complex ((HCOO)2Ni(2EHA)2), and may be, for example, either (HCOO)2Cu(2EHA)2 alone, (HCOO)2Ni(2EHA)2 alone, or a mixture of (HCOO)2Cu(2EHA)2 and (HCOO)2Ni(2EHA)2.

[0025] In addition, it is preferable that the water content of the metal complex ink is 20% by mass or less. Water tends to form a structure in which it is trapped within a colloid formed by the aggregation of multiple micelles of the metal complex. Therefore, the size of the colloid varies depending on the amount of water trapped within the colloid. In addition, not only does the amount of trapped water differ for each colloid, but the water trapped in the colloid is eluted from the colloid to the ethylene glycol side over time after the metal complex ink is produced, so the size of the colloid decreases over time. Furthermore, the behavior of the colloid's size decreasing varies depending on the environment, such as the temperature, in which the metal complex ink is stored.

[0026] That is, if water is contained in the metal complex ink, the size of the colloid is unstable, and as a result, there is a risk of variation in the particle size and shape of the metal particles. Therefore, by having a low water content in the metal complex ink, the properties of the metal complex are stabilized, and the variation in the particle size and shape of the metal particles can be controlled. Specifically, as described above, the water content of the metal complex ink is sufficient as long as it is 20 mass% or less, and the lower limit of the water content is preferably 0 mass%, but the lower limit may be the detection limit of an analytical instrument, etc.

[0027] In addition, the ethanol content of the metal complex ink is preferably 50% by mass or less. Since ethanol is compatible with water, the presence of ethanol increases the water content of the metal complex ink, and as described above, the size of the colloid is unstable due to water, which may result in variation in the particle size and shape of the metal particles.

[0028] Therefore, by having a low ethanol content in the metal complex ink, the properties of the metal complex are stabilized, and the variation in particle size and shape of the metal particles can be controlled. Specifically, as described above, the ethanol content in the metal complex ink is required to be 50% by mass or less, and the lower limit of the ethanol content is preferably 0% by mass, but the lower limit may be the detection limit of an analytical instrument or the like.

[0029] [Metal complex ink manufacturing method] Next, a method for producing a metal complex ink will be described. The method includes the following first mixing step. It may also include a second mixing step and a dehydration step.

[0030] <First mixing process> The first mixing step is (HCOO) m This process involves mixing a metal formate represented by Me·nH2O with ethylene glycol and 2-ethylhexylamine. The purpose of this process is to coordinate the amino group of 2-ethylhexylamine to the metal of the metal formate to form a metal complex such as (HCOO)2Me(2EHA)2.

[0031] Ethylene glycol is a dispersion medium that disperses colloids formed by the aggregation of micelles of metal complexes. Since 2-ethylhexylamine does not dissolve in ethylene glycol, the metal complexes coordinated with 2-ethylhexylamine do not dissolve in ethylene glycol either, and the micelles of the colloidal metal complexes are dispersed in ethylene glycol in the form of an emulsion.

[0032] In the metal formate, Me is Cu or Ni. Then, m is 2, and n is 4 when Me is Cu, and 2 when Me is Ni. That is, as the metal formate, (HCOO)2Cu 4H2O or (HCOO)2Ni 2H2O can be used. Note that, as the metal formate, only (HCOO)2Cu 4H2O or only (HCOO)2Ni 2H2O may be used.

[0033] The specific method for mixing the metal formate, ethylene glycol, and 2-ethylhexylamine is not particularly limited. For example, these raw materials may be mixed in a container. As an example, ethylene glycol may be placed in a beaker and stirred with a stirrer, and the metal formate and 2-ethylhexylamine may be added thereto. In addition, these raw materials may be mixed in a rotation-revolution type mixer.

[0034] <Second mixing process> The second mixing step is a step of mixing metal formate and ethanol before the first mixing step. The mixing method is not particularly limited, and these raw materials may be put into a container and stirred. As described above, metal formate is a hydrate and contains water, so the size of the colloid is not stable, which may result in variation in the particle size and shape of the metal particles, so it is preferable to remove water.

[0035] The water is actually removed in the dehydration step described below, but by mixing ethanol, which is compatible with water, with the metal formate in advance, the water can be removed by entraining it with the ethanol. The reason why this second mixing step is performed before the first mixing step is that if a colloid is formed by the metal complex in the first mixing step, the water derived from the hydrate will be trapped within the colloid, making it difficult to remove the water. By bringing the water derived from the hydrate of the metal formate into contact with ethanol before the colloid is formed, dehydration becomes easier.

[0036] <Dehydration process> The dehydration step is a step of dehydrating the mixture obtained by the first mixing step under reduced pressure after the first mixing step. The mixture specifically contains the metal complex that has become a colloid, ethylene glycol for dispersing the colloid, water, and ethanol. When this mixture is dehydrated under reduced pressure, the ethanol, which has a low boiling point, is preferentially evaporated, but water can also be evaporated together with the ethanol, i.e., the mixture can be dehydrated.

[0037] The size of the colloids varies depending on the amount of water trapped within the colloids. Not only does the amount of trapped water differ for each colloid, but the water trapped in the colloids dissolves from the colloids into the ethylene glycol over time after the metal complex ink is created, causing the size of the colloids to decrease over time. Furthermore, the behavior of the colloids decreasing in size varies depending on the environment, such as the temperature, in which the metal complex ink is stored.

[0038] Therefore, if the second mixing step and the dehydration step are not performed, the size of the colloids will vary and become unstable depending on the amount of trapped water. However, by performing the second mixing step and the dehydration step, the water trapped in the colloids can be sufficiently removed, making it possible to stabilize the size of the colloids uniformly and without variation over the long term.

[0039] The method of dehydration is not particularly limited, but a specific method is to heat, stir, and place the mixture under reduced pressure in an evaporator to dehydrate it. Ethanol is also removed together with water.

[0040] [Metal particle manufacturing method] Next, the method for producing metal particles of the present invention will be described. This method includes the following heating step.

[0041] <Heating process> The heating step is a step of heating the above-mentioned metal complex ink of the present invention, which decomposes the metal complex to obtain metal particles and removes the ethylene glycol.

[0042] Taking (HCOO)2Cu 4H2O as an example, it is sufficient to heat the material under conditions in which the divalent copper in (HCOO)2Cu 4H2O is reduced to zero-valent copper to form copper particles, and also to heat the material under conditions in which the ethylene glycol can be volatilized and removed.

[0043] For example, the metal complex ink can be heated to 70° C. to 250° C. in an inert atmosphere using a gas such as nitrogen or argon to prevent the copper from oxidizing, thereby reducing the copper to produce copper particles.

[0044] When the metal is Ni, metal particles can also be obtained by heating the metal complex ink under similar conditions to those for Cu, with the heating temperature and heating atmosphere being appropriately adjusted.

[0045] [Metal sintered film manufacturing method] Next, a method for producing a metal sintered film of the present invention will be described. This method includes the following printing step and heating step.

[0046] <Printing process> The heating step is a step of printing the metal complex ink of the present invention in the form of a thin film. The printing target is a substrate, for example a copper substrate or an alumina substrate, which is covered with a metal mask, the openings of the metal mask are filled with the metal complex ink, and then the metal mask is removed to form a thin film having the same thickness as the thickness of the metal mask.

[0047] <Heating process> The heating process is a process in which the thin film obtained by the printing process is sintered to obtain a metal sintered film. Heating is performed in an inert gas atmosphere such as nitrogen gas so that the metal does not oxidize during sintering. The heating conditions are conditions under which the metal sinters, and for example, a metal sintered film can be obtained by heating the thin film at 250°C for 10 minutes. EXAMPLES

[0048] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the examples. A copper complex ink was prepared, and then copper particles were prepared using the copper complex ink. The shape of the prepared copper particles was observed.

[0049] [Raw materials used] Copper formate tetrahydrate ((HCOO)2Cu·4H2O) (Fujifilm Wako Pure Chemical Industries, Ltd.), 2-ethylhexylamine, 2-amino-2-methyl-1-propanol, ethanol, and ethylene glycol (all from Nacalai Tesque, Inc.) were used.

[0050] [Example 1] <Production of copper complex ink> (Second mixing process) 2 g of copper formate tetrahydrate and 0.5 g of ethanol were placed in a container and mixed.

[0051] (1st mixing step) 0.5g of ethylene glycol and 1.06g of 2-ethylhexylamine were added to the above container and mixed to synthesize (HCOO)2Cu(2EHA)2, and a dispersion was obtained in which a colloid formed by the aggregation of micelles of the copper complex was dispersed in ethylene glycol. Mixing was performed at room temperature (25°C) using a stirrer (ARE-310, manufactured by Thinky Corporation).

[0052] <Dehydration process> The above dispersion was transferred from the container to a recovery flask, and an evaporator was used to cause azeotropy between water and ethanol, and the mixture was thoroughly dehydrated until no evaporation of these was observed, thereby obtaining the copper complex ink of Example 1.

[0053] <Production of copper particles> A portion of the produced copper complex ink was sampled and heated to 150°C to form copper particles while the ethylene glycol remained. A separate sample of the copper complex ink was applied to a copper plate and heated to 180°C in a vacuum to form copper particles and remove the ethylene glycol by volatilization.

[0054] Observation of copper particles The copper complex ink and the copper complex ink sample after heating to 150°C were magnified 100 times with an optical microscope to confirm their condition. In addition, the copper particles obtained by heating to 180°C in a vacuum were observed with a SEM (scanning electron microscope). The magnified image with the optical microscope is shown in Figure 1, and the image observed with the SEM is shown in Figure 3.

[0055] (Cross-sectional observation of the formed copper sintered film) The copper complex ink produced was printed on a copper plate using a metal mask in the form of a thin film, and then heated to 250°C for 10 minutes in nitrogen gas to obtain a copper sintered film. The cross section of this copper sintered film was observed by SEM. The cross-sectional image observed by SEM is shown in Figure 5.

[0056] [Comparative Example 1] <Production of copper complex ink> 2g of copper formate tetrahydrate, 0.5g of ethylene glycol, and 2g of 2-amino-2-methyl-1-propanol (hereinafter referred to as "AMP") were put into a container and mixed to synthesize (HCOO)2Cu(2AMP)2, thereby obtaining a copper complex ink. Mixing was performed at room temperature (25°C) using a mixer (ARE-310 manufactured by Thinky Corporation). The second mixing step and dehydration step were not performed.

[0057] <Production of copper particles> Copper particles were produced under the same conditions as in Example 1.

[0058] Observation of copper particles The copper complex ink and copper particles were observed with an optical microscope and an SEM under the same conditions as in Example 1. An enlarged image taken with an optical microscope is shown in Figure 2, and an image observed with an SEM is shown in Figure 4.

[0059] (Cross-sectional observation of the formed copper sintered film) A copper sintered film was produced under the same conditions as in Example 1, and the cross section of the copper sintered film was observed by SEM. The cross section observation image by SEM is shown in FIG.

[0060] [result] (State of copper complex ink) From Fig. 1(A), it was confirmed that the copper complex ink of Example 1 was in a state where a colloid formed by aggregation of micelles of the copper complex was stably dispersed in ethylene glycol. On the other hand, from Fig. 2(A), it was confirmed that, since the copper complex ink of Comparative Example 1 has the property of dissolving AMP in ethylene glycol, the copper complex was dissolved in ethylene glycol while the undissolved copper complex was present in the form of particles.

[0061] (State of copper complex ink sample after heating to 150℃) From Fig. 1(B), it was possible to confirm the presence of spot-like aggregates of copper particles in the sample of Example 1, but because the individual copper particles were small, a magnification of 100 times was not sufficient, and the state of the copper particles could not be clearly confirmed with an optical microscope. On the other hand, from Fig. 2(B), it was confirmed that the sample of Comparative Example 1 contained small copper particles in the form of fragments and large rod-like clumps of copper particles with a longitudinal direction, and that the size and shape of the copper particles varied greatly.

[0062] (State of copper particles after heating to 180℃) As can be seen from Fig. 3, the copper particles of Example 1 were roughly granular with a particle diameter of about 10 nm, and were uniform particles. On the other hand, as can be seen from Fig. 4, the copper particles of Comparative Example 1 were a mixture of roughly granular particles with a particle diameter of about 100 nm to 700 nm and large, irregularly shaped, clump-like particles, and it was confirmed that the copper particles varied greatly in size and shape.

[0063] (Cross-section observation of copper sintered film after heating at 250℃ after printing) In the copper sintered film of Example 1 shown in FIG. 5, although some copper nanoparticles from the sintering process were observed on the upper side of the printed film, it was an almost uniform sintered film, whereas in the copper sintered film of Comparative Example 1 shown in FIG. 6, coarse copper particles were generated at the bottom of the printed film, and the particle size became smaller toward the top of the printed film, and large particles of irregular shapes were sintered together, confirming that the sintered film was non-uniform.

[0064] As described above, the present invention is industrially useful because it stabilizes the properties of the metal complex, makes it possible to control variations in the particle size and shape of the metal particles, and enables the uniform particles to increase the coating film density and produce a uniform sintered film.

Claims

1. (HCOO) 2 Me (2EHA) 2 A colloid formed by assembling micelles of a metal complex represented by the formula: ethylene glycol in which the colloid is dispersed; A metal complex ink comprising: Me is Cu or Ni; The metal complex ink, wherein 2EHA is 2-ethylhexylamine.

2. The metal complex is (HCOO) 2 Cu(2EHA) 2 , (HCOO) 2 Ni(2EHA) 2 , or (HCOO) 2 Cu(2EHA) 2 and (HCOO) 2 Ni(2EHA) 2 The metal complex ink of claim 1 , which is a mixture of

3. 3. The metal complex ink according to claim 1, wherein the water content is 20% by mass or less and the ethanol content is 50% by mass or less.

4. (HCOO) m Me.nH 2 A first mixing step of mixing a metal formate represented by formula (I) O, ethylene glycol, and 2-ethylhexylamine, The Me is either Cu or Ni, The m is 2, A method for producing a metal complex ink, wherein n is 4 when Me is Cu, and n is 2 when Me is Ni.

5. a second mixing step of mixing the metal formate with ethanol before the first mixing step; The method for producing a metal complex ink according to claim 4 , further comprising, after the first mixing step, a dehydration step of dehydrating the mixture obtained in the first mixing step under reduced pressure.

6. The metal formate is (HCOO) 2 Cu.4H 2 O only, or (HCOO) 2 Ni・2H 2 The method for producing a metal complex ink according to claim 4 or 5, wherein the metal complex is O alone.

7. 3. A method for producing metal particles, comprising the step of heating the metal complex ink according to claim 1, wherein the heating step is a step of decomposing the metal complex to obtain metal particles and removing ethylene glycol.

8. A printing step of printing the metal complex ink according to claim 1 or 2 into a thin film; The method for producing a metal sintered film includes a heating step of heating the thin film obtained by the printing step in nitrogen gas and holding it at 250° C. for 10 minutes to obtain a metal sintered film.

Citation Information

Patent Citations

  • Method for producing nickel particle and nickel complex suitably used therein

    JP2010064983A

  • Copper-nickel nanoparticle, and method for producing the same

    JP2011063828A

Cited By

  • Method for producing copper complex ink

    WO2026048694A1